Psychological Predictors of Bullying in Adolescents From Pluricultural Schools: A Transnational Study in Spain and Ecuador - Rodríguez-Hidalgo, Antonio J.; Pantaleón, Yisela; Calmaestra, Juan (Frontiers in Psychology, 2019)
This study aimed to analyze the levels of personal aggression and victimization, ethnic-cultural aggression and victimization, self-esteem, empathy, social skills and gender in adolescents as potential predictors of bullying in Spain and Ecuador. The wide pluricultural sample comprised Secondary Education students from both countries (N = 25190, average age = 13.92, SD = 1.306; NSpain = 14437; NEcuador = 10753), who took part in the study by filling in a self-report. The results revealed that predictive models of bullying for both countries explain 50-70% of variance. A transnational predictive pattern of personal victimization can be observed based on the levels of ethnic-cultural victimization, ethnic-cultural aggression, personal aggression, self-deprecation and affective empathy. A transnational predictive pattern of personal aggression is evidenced depending on the levels of ethnic-cultural aggression, personal victimization, self-deprecation, ethnic-cultural victimization and the fact of being female. We concluded that bullying can largely be predicted by involvement in ethnic-cultural discrimination. These results are discussed, and educational inferences are drawn for prevention.